Temporal and region-specific effects of sleep fragmentation on gut microbiota and intestinal morphology in Sprague Dawley rats. (3rd July 2020) - Triplett, Judy; Ellis, David; Braddock, Amber; Roberts, Erin; Ingram, Katherine; Perez, Eric; Short, Amanda; Brown, Dominique; Hutzley, Victoria; Webb, Chelsey; Soto, Armando; Chan, Victor
ABSTRACT: Sleep is a fundamental biological process, that when repeatedly disrupted, can result in severe health consequences. Recent studies suggest that both sleep fragmentation (SF) and dysbiosis of the gut microbiome can lead to metabolic disorders, though the underlying mechanisms are largely unclear. To better understand the consequences of SF, we investigated the effects of acute (6 days) and chronic (6 weeks) SF on rats by examining taxonomic profiles of microbiota in the distal ileum, cecum and proximal colon, as well as assessing structural and functional integrity of the gastrointestinal barrier. We further assayed the impact of SF on a host function by evaluating inflammation and immune response. Both acute and chronic SF induced microbial dysbiosis, more dramatically in the distal ileum (compared to other two regions studied), as noted by significant perturbations in alpha- and beta-diversity; though, specific microbial populations were significantly altered throughout each of the three regions. Furthermore, chronic SF resulted in increased crypt depth in the distal ileum and an increase in the number of villi lining both the cecum and proximal colon. Additional changes were noted with chronic SF, including: decreased microbial adhesion and penetration in the distal ileum and cecum, elevation in serum levels of the cytokine KC/GRO, and depressed levels of corticotropin. Importantly, our data show that perturbations to microbial ecology and intestinal morphology intensify in response to prolonged SF and these changes are habitat specific. Together, these results reveal consequences to gut microbiota homeostasis and host response following acute and chronic SF in rats.